Quantification of students’ active learning in design, build, and test engineering modules - Milisavljevic-Syed, Jelena (University of Liverpool, 2023)
The focus in this paper is to address the primary research question ‘How can instructors leverage assessment tools in design, build, and test modules to quantify students’ active learning well enough to improve modules for future students?’ In the engineering module, Product Design Group Project (PDGP), the primary goal is to enable students to internalize five principles of engineering design (POED), wherein each assignment students are tasked with writing learning statements (LS). LS captures how much students internalize the target POED and formulate an understanding of how to apply this knowledge moving forward. Each academic year in the PDGP module, at a university in north-west England, around 780 LS are consented by module students. In this paper, a flexible text mining framework is used to process LS and analyse students’ learning and improve the delivery of design, build, and test engineering modules, such as the PDGP.
Keywords: active learning; learning statements; text mining; self-reflection; assessment tool